A new species of Wahydra from Ecuador (Hesperiidae, Hesperiinae, Anthoptini) - Carneiro, Eduardo; Dolibaina, Diego R.; Grishin, Nick V.; Warren, Andrew D. (Zootaxa, 2018)
Recent taxonomic studies on the genus Wahydra Steinhauser, 1991, have described five new species in the past two years, from high elevations in the Andes Mountains. A markedly distinct species of Wahydra is herein described and illustrated based on a single male specimen from Ecuadorian Andes, Wahydra graslieae A. Warren, Carneiro & Dolibaina, sp. nov. The new species is compared with other species of Wahydra, as well as with the somewhat similar species Lerema viridis (Bell, 1942) and Tigasis viridenex (Weeks, 1901).